The application of new technologies to remote interpreting - Connell, Tim (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Changes in language needs and language policies have had an impact on the provision of services which require access to interpreting. It is perhaps inevitable that new professional areas such as community inter - preting1 should look to new technologies in the search for solutions to particular problems or (on a more positive note) to provide more effi - cient services. This article suggests that there is ample scopefor the extension of such services by the application of new technologies. Such a process will, however, have an impact on both the practical and ethical aspects of the interpreter's work.